Tinjauan Rencana Anggaran Biaya (RAB) Pondasi Tiang Pancang (studi kasus ; Pembangunan gedung kantor Gubernur Prov. Sulawesi Tenggara Tahap 1 - Muhamad Ronaldi; Sulha; Masdiana Masdiana (MEDIA KONSTRUKSI, 2024)
The project budget plan involves calculating the estimated costs for a building, including wages and other expenses related to project implementation. This research aims to determine the extent of the difference between the Budget Plan (Rencana Anggaran Biaya or RAB) for Pile Foundation according to AHSP PUPR No. 1 Year 2022 and the actual Budget Plan in the field. Additionally, it seeks to identify the factors influencing the differences in the Budget Plan for Pile Foundation work. The study involves analyzing working drawings and budget plans by recalculating unit prices using AHSP PUPR No. 1 Year 2022 and the prices of materials and services in Kendari city in 2022. Data was collected directly at the project site for analysis to draw conclusions from the research. The research findings indicate that the Budget Plan for Pile Foundation work, according to the Unit Price of Goods and Services from the Government of Kendari City for the year 2022, is Rp. 11,954,048,000.00 (Eleven Billion Nine Hundred Fifty-Four Million Forty-Eight Thousand Rupiah), while the actual Budget Plan for Pile Foundation work in the field is Rp. 12,410,060,000.00 (Twelve Billion Four Hundred Ten Million Sixty Thousand Rupiah). There is a difference of Rp. 456,000,000.00 (Four Hundred Fifty-Six Million Rupiah) between the two budgets. Factors influencing the differences in the Budget Plan for Pile Foundation work include errors in field implementation due to a lack of worker experience, weather conditions, and decreased productivity of pile-driving equipment.